Accuracy of transrectal ultrasonography: In estimating the gestational age of Jamnapari goats - Faisal Abubakar,; Asmad Kari,; Zawawi Ismail,; Abdul Rashid Baba,; Tijjani Haruna Usman, (Malaysian Society of Applied Biology, 2016)
The precise identification of early pregnancy in farm animals especially small ruminants, plays a significant role in the effective reproductive management of the herd. Early pregnancy diagnosis and foetal measurements of Jamnapari does were carried out using a transrectal probe of B-mode real-time ultrasonography, on a weekly basis starting from day 28 to 100 of gestation age. All the scanning results were recorded. The sensitivity (Se) was 60-95% and specificity (Sp) 50-75% at day 56 respectively. However, the relationship between the ultrasonic foetal parameters and gestational age were highly (P<0.01) correlated, although biparietal diameter BPD (0.980) was strongly correlated to gestation age than crown-rump length (CRL) (0.969). In conclusion, the ultrasound early pregnancy diagnosis can be considered a reliable and convenient means for early pregnancy detection. The measurements of CRL and BPD were proven to be an efficient parameters for predicting gestational age in Jamnapari goats.